Assessment of the degree of dyspnea in patients with bilateral advanced destructive tuberculosis after staged bilateral extrapleuralpneumolysis with silicone plombage - D. V. Donchenko; M. I. Chushkin; E. V. Krasnikova; M. A. Bagirov (Лечащий Врач, 2024)
Background. The number of patients with bilateral was destructive pulmonary tuberculosis. In Russian Federation, the number of patients with bilateral advanced destructive pulmonary tuberculosis has increased, which is due to an increase in cases of drug-resistant pathogens. Such patients often have low respiratory parameters clinically manifested by dyspnea, which is the main reason for a decrease in exercise tolerance and of deterioration in the quality of life.Objective. The objective of this study is to assess the dynamics of the degree of dyspnea in patients with bilateral advanced destructive tuberculosis after staged bilateral extrapleural pneumolysis with silicone plombage.Material and methods. The study included 11 patients with bilateral advanced destructive pulmonary tuberculosis who underwent staged bilateral extrapleural pneumolysis with silicone plombage (main group) and 8 patients who underwent consecutive bilateral lung resections (control group). The mMRC scale and the Borg scale were used to assess dyspnea.Results. The degree of dyspnea on the mMRC scale in the main group decreased by 0,4 ± 0,1, and in the control group one increased by 0,9 ± 0,5 (p < 0,001). When assessing dyspnea on the Borg scale, a decrease of 0,3 ± 0,5 points was revealed in the main group, an increase of 2,5 ± 0,4 point in the control group (p < 0,001).Conclusion. Staged bilateral extrapleural pneumolysis with silicone plombage may be accompanied by decrease in the degree of dyspnea, to a lesser extent than after lung resection and therefore collapse surgery is more preferable in patients with low exercise capacity.